40 on Justice: The Prophetic Voice on Social Reform. Book Review by Abdulkadir Salaudeen - Abdulkadir Salaudeen (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
Author                        : Omar Suleiman Book Title                 : 40 on Justice: The Prophetic Voice on Social Reform ISBN                           : 1847741436; 978-1847741431 Publisher                   : Kube Publishing Ltd Place of Publication : United Kingdom Page Number            : 338 Price                           : $24.13 Year of Publication  : 2021 Reviewer                    : Abdulkadir Salaudeen